Improving the Quality of Smoked Fish Processing for the PKM Program in Hamadi Village, Jayapura City - Basa T. Rumahorbo; Diana M. Abulais; Hardi Hamzah; Daniel ZK Wambrauw; Lolita Tuhumena; Yulindra M. Numberi; Sara Umbekna; Nicea R. Paranoan (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Smoked fish products produced by fishing households in Jayapura City are widely known, becoming food products that are popular with city residents and souvenirs for tourists. The development of this superior commodity requires at least four requirements, namely that commodity procurement must be continuous in quantity, quality and at the right time, have good traceability, continuous development and mastery of technology, and adequate mastery of business management. It is within this framework that this community service activity is carried out. The aim of this Community Partnership Service activity is to empower the community to increase their knowledge and skills in using appropriate fish smoking equipment, making hygienic packaging, understanding production and marketing management and making simple cash books in running a smoked fish processing business in Hamadi Village, Jayapura City. This service uses participatory rural appraisal methods, fisheries education, and pretest posttest control group design. Based on the results of the implementation of activities with POKLAHSAR Mama Papua partners on 26-27 August and 22-23 September 2023, it is known that there is an understanding of cash bookkeeping, the use of appropriate smoking equipment, production management and marketing management, as well as making hygienic packaging for smoked tuna. , has increased. It is hoped that this can become a benchmark for the development of the smoked fish business among partners as targeted in the activity objectives.